(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2010)
The oil obtained by the hydro-distillation method from the fresh leaves and stems of Anethum sowa L. (Dill) herb was analyzed by GC-MS. Twenty compounds were isolated and identified. The major constituents were apiole (25.39%), o-cymene (15.25%), α-thujene (14.84%), β-phellandrene (7.17%), 6,6-dimethyl-2-(3-oxobutyl) bicyclo(3.1.1) heptan-3-one (6.90%), exo-2-hydroxycineol (5.03%), limonene (4.13%), 3-isopropyl-4-methyl-1-pentyn-3-ol (2.89%), myristicine (2.46%) and dihydroumbellulone (2.14%). Key words: Anethum sowa L.; Essential oil; GC-MS; Apiole DOI: 10.3329/bjsir.v45i2.5721 Bangladesh J. Sci. Ind. Res. 45(2), 173-176, 2010